2010
DOI: 10.1126/scitranslmed.3000976
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Neurons Mediate Dyskinesia Side Effects in Parkinson’s Patients with Neural Transplants

Abstract: Troublesome involuntary movements in the absence of dopaminergic medication, so-called off-medication dyskinesias, are a serious adverse effect of fetal neural grafts that hinders the development of cell-based therapies for Parkinson's disease. The mechanisms underlying these dyskinesias are not well understood, and it is not known whether they are the same as in the dyskinesias induced by l-dopa treatment. Using in vivo brain imaging, we show excessive serotonergic innervation in the grafted striatum of two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
279
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 294 publications
(296 citation statements)
references
References 36 publications
10
279
1
6
Order By: Relevance
“…4 Recent research indicates that serotonin also plays a crucial role in PD, especially in PD treatment. 5,6 The detection of these two neurotransmitters especially serotonin remains challenging mainly due to their low basal concentrations in the vicinity of neuronal junctions (10 −9 to 10 −6 M). 7 The voltammetric method gains its popularity in detecting oxidizable biogenic amines.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…4 Recent research indicates that serotonin also plays a crucial role in PD, especially in PD treatment. 5,6 The detection of these two neurotransmitters especially serotonin remains challenging mainly due to their low basal concentrations in the vicinity of neuronal junctions (10 −9 to 10 −6 M). 7 The voltammetric method gains its popularity in detecting oxidizable biogenic amines.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…It has been found that transplantation of the abovementioned tissue can improve movement related problems in PD patients [38]. In a relevant study, it was found that the motor symptoms can improve even for eighteen years after transplantation [39,40]. In addition, some studies exist which showed contradictory results which oppose the above findings [41,42].…”
Section: Mesencephalic Tissue Of the Human Fetusmentioning
confidence: 64%
“…Two recent studies [45] of transplanted PD patients have provided support for this idea [46]. These studies included 3 patients who had received fetal mesencephalic grafts 13 to 16 years earlier.…”
Section: Adverse Effects Are Few With Dopaminergic Grafts Except Dysmentioning
confidence: 99%
“…Moreover, several patients whose brains have become available for analysis at autopsy have provided a unique opportunity to study the survival and function of the grafted dopaminergic neurons at survival times for as much as 22 years. Some of these patients, such as the 3 reported in the recent studies [45] and [46] have shown sustained clinical benefit of their transplants for more than 13 years, although in these cases it was associated with the emergence of dyskinesias (GIDs) unrelated to their ongoing medication. The recovery in striatal 18 F-DOPA uptake seen in these patients has been sustained, suggesting that the grafted dopaminergic neurons have survived well over time.…”
Section: Can Neural Grafts Survive and Provide Long-term Function?mentioning
confidence: 99%